2012
DOI: 10.1080/15226514.2011.560212
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bermudagrass Cultivars for Phytoremediation of Petroleum Contaminated Soils

Abstract: Phytoremediation is an alternative to other technologies for the clean up of petroleum contaminated soil. Ten vegetatively propagated cultivars of bermudagrass were examined for their potential to reduced oil sludge contaminated in soil and select the most efficient cultivar. Soil was mixed with different rates of oil sludge (0, 10, 20, 30, and 40% (w/w) to obtain 0, 2, 4, 6, and 8% total petroleum hydrocarbons (TPHs). Ten cultivars of bermudagrass were planted in pots filled with respected mixtures of soil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Merkl et al 21, 22 showed enhanced degradation of crude oil under the influence of a tropical grass after only a few months, Muratova et al 23 showed TPH reduction up to 52% during 3 years of rye cultivation. Razmjoo and Adavi24 found 40% TPH reduction by bermudagrass cultivars in petroleum contaminated soils after 6 months. In the present study, A. compressus decreased TPH by 70% in TA and 40% in TC compared with 11% and 9% in TB and TD, respectively, over the 360 days.…”
Section: Resultsmentioning
confidence: 99%
“…Merkl et al 21, 22 showed enhanced degradation of crude oil under the influence of a tropical grass after only a few months, Muratova et al 23 showed TPH reduction up to 52% during 3 years of rye cultivation. Razmjoo and Adavi24 found 40% TPH reduction by bermudagrass cultivars in petroleum contaminated soils after 6 months. In the present study, A. compressus decreased TPH by 70% in TA and 40% in TC compared with 11% and 9% in TB and TD, respectively, over the 360 days.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Muratova et al 25 reported up to 52% reduction in oil and grease contents during three years of rye cultivation. Additionally, Razmjoo et al 26 found 40% reduction in TOG levels by employing Bermuda grass by the end of six months of experimental trials. www.nature.com/scientificreports/ Soil enzyme activity and beneficial bacterial population.…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, the increase in average root biomass, compared to a corresponding decrease in average shoot biomass, in response to increasing mineral oil suggests the plant put more energy into root growth than shoot growth due to stress induced by oil contamination. Oil can not only reduce the amount of water and oxygen available for plant growth (Kaur et al, 2017) but also can interfere with plant-water relations by direct physical contact (coating of root tissues) thus negatively affecting shoot growth (Razmjoo and Adavi, 2012). Such phenomena affect the local biogeochemistry, for example changing nutrient dynamics (Xu and Johnson, 1997) which in turn cause changes in root morphology similar to those observed here (Franco et al, 2011;Hermans et al, 2006).…”
Section: Resultsmentioning
confidence: 65%